Health psychology a cultural approach - Gurung, Regan A. R. (Wadsworth Cengage Learning, 2014)
Introduces students to health psychology with an integrated cultural perspective. This book focuses on key determinants of behavior - such as family, ethnicity, and religion. It provides students with a comprehensive description of basic theories and an overview of cutting-edge research in health psychology.